Man's dominion : religion and the eclipse of women's rights in world politics - Jeffreys, Sheila (Abingdon, Oxon ; New York : Routledge, 2012)
"This book seeks to rekindle the criticism of religion as the founding ideology of patriarchy. Focusing on the three monotheistic religions: Judaism, Christianity and Islam, this book examines common anti-woman attitudes such as 'male-headship', impurity of women, the need to control women's bodies, and their modern manifestations in multicultural Western states"--Back cover.
The devil's gateway: religion and the subordination of women -- Fundamentalism: the divine right of patriarchs -- Right to religion trumps women's human rights -- Multiculturalism and '̀respect' for religion -- Desecularisation and women's equality -- Covering up women -- A harem for every man? The rise of polygamy -- The master's tools: Islamic feminism and its critics.
Includes bibliographical references (pages [197]-217) and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Sex discrimination against women; Patriarchy; Religion and politics; Religion -- Social aspects; Human rights; Electronic books